Mengedukasi Mata Uang Cryptocurrency Kepada Mahasiswa Binadarma - Wahyu Firmansyah; Tata Sutabri; Dwi Desi Yanti; Nabila Amelia Pratiwi (Akuntansi, 2023)
Cryptocurrency is a form of digital currency that uses cryptographic technology for security and operates independently without a central bank. Cryptocurrencies offer several benefits compared to traditional currencies, including decentralization, security, anonymity, and accessibility. However, cryptocurrencies also carry some risks, including volatility, security, and regulation. This research aims to educate students about cryptocurrency and how they can get involved with cryptocurrency. The research method used is literature review, using library materials as the main source, meaning that the data is collected from the literature, whether in the form of journals, online media, books and others. Which is still related to cryptocurrency. The research results show that students can engage with cryptocurrencies by purchasing them, mining them, or accepting them as payment. However, students should also understand the risks associated with cryptocurrencies and do research before getting involved in cryptocurrency investments..